Evidence for and cost‐effectiveness of physiotherapy in haemophilia: a Dutch perspective. (6th September 2016) - de Kleijn, P.; Mauser‐Bunschoten, E. P.; Fischer, K.; Smit, C.; Holtslag, H.; Veenhof, C.
Abstract : Introduction: Musculoskeletal impact of haemophilia justifies physiotherapy throughout life. Recently the Dutch Health Care Institute constrained their 'list of chronic conditions', and withdrew financial coverage of physiotherapy for elderly persons with haemophilia (PWH). This decision was based on lack of scientific evidence and not being in accordance with 'state of science and practice'. Methods: In general, evidence regarding physiotherapy is limited, and especially in rare diseases like haemophilia. 'Evidence based medicine' classifies and recommends evidence based on meta‐analyses, systematic reviews and randomized controlled trials, but also means integrating evidence with individual clinical expertise. For the evaluation of physiotherapy – usually individualized treatment – case studies, observational studies and Case Based Reasoning may be more beneficial. Results: Overall annual treatment costs for haemophilia care in the Netherlands are estimated over 100 million Euros, of which 95% is covered by clotting factor concentrates. The cost for physiotherapy assessments in all seven Dutch HTCs (seven centres for adult PWH and seven centres for children) is limited at approximately 500 000 Euros annually. Costs of the actual physiotherapy sessions, carried out in our Dutch first‐line care system, will also not exceed 500 000 Euros. Thus, implementation of physiotherapy in haemophilia care the Netherlands in a most optimal way would cost less than 1% of the total budget. Aim: The present paper describes the role of physiotherapy in haemophilia care including available evidence and providing suggestions regarding generation of evidence. Establishing the effectiveness and cost‐effectiveness of physiotherapy in haemophilia care is a major topic for the next decennium.